The role of job satisfaction in preschool teachers' well-being: A structural equation modeling analysis - Wan Idris, Wan Izani; Hermawati, Desi; Hidayat, Riyan; Nasir, Nurihan (Eurasian Society of Educational Research, 2023)
Teacher well-being is a stimulating topic frequently appearing in studies over long periods. Teachers are typically exposed to stress that, when addressed, can lead to low morale and positively impact their work. This study examined the relationship between job satisfaction and well-being among preschool teachers in Selangor. We used a quantitative research method and correlational research design to test the hypotheses and answer the research questions. The current study involved 977 government preschool teachers selected using a cluster random sampling method. After data cleaning, a data set of 610 respondents was used for this study. This study used exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) using AMOS for data analysis. SEM Analysis showed that job satisfaction positively influences teachers' well-being. However, our results also showed that the subconstruct of job satisfaction with students did not significantly influence preschool teachers' well-being.